The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4172/2155-9589.1000151
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of Corrugated Feed Channel of Direct Contact Membrane Distillation

Abstract: Membrane distillation is a hybrid process in which the separation process is based on both thermal potential and membrane characteristics. However, some technical challenges such as thermal boundary layer builds up (temperature polarization) resulted in low mass flux. In this study, the direct contact membrane distillation is equipped with corrugated feed channel to create fluid mix for mass flux improvement. A lab scale flat sheet membrane distillation is assembled with corrugated feed channel to suppress the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Another route to mitigating the polarization effects is increasing the chaotic state of the flow near the membrane surface, such as increasing the feed velocity and using pulse flow [22,23] or filling the spacers in the flow channels [24][25][26][27]. It has been reported that changing the geometry of the MD module channel is an effective approach to increasing the chaotic state of feed and coolant [28][29][30][31]. Kuang et al have researched the potential of adding baffles on flow channels to enhance direct contact membrane distillation (DCMD) performance [32].…”
Section: Introductionmentioning
confidence: 99%
“…Another route to mitigating the polarization effects is increasing the chaotic state of the flow near the membrane surface, such as increasing the feed velocity and using pulse flow [22,23] or filling the spacers in the flow channels [24][25][26][27]. It has been reported that changing the geometry of the MD module channel is an effective approach to increasing the chaotic state of feed and coolant [28][29][30][31]. Kuang et al have researched the potential of adding baffles on flow channels to enhance direct contact membrane distillation (DCMD) performance [32].…”
Section: Introductionmentioning
confidence: 99%